2022
DOI: 10.1097/md.0000000000030919
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of maxillary incisor retraction effects for patients with first premolar extractions between Damon Q and Invisalign®: A retrospective study

Abstract: Torque control of maxillary incisors is very important in maxillary protrusion patients with first premolars extraction, but the efficacy of maxillary incisor retraction of clear aligners is still controversial now. This retrospective study was aimed to compare the retraction effects between Damon Q and Invisalign ® appliances in patients with first premolar extractions. 59 patients (33 cases with Damon Q and 26 cases with Invisalign ® ) with first premolar extraction were selected in this study. Subsequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…[20,24]Conversely, other studies concluded that torque measurements obtained from cephalometric are predictable for clinical purposes. [7] The cephalometric analysis (T0-T1) shows that CAs are effective in retracting the maxillary incisors and improving the pro le, which is consistent with previous studies. [7]However, the angle changes of the maxillary incisors decreased by 11.68° from T0-T1, and the post-U1-NA(°)was less than the standard deviation of the normal mean, indicating that CAs were not effective in controlling incisor torque in extraction cases.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…[20,24]Conversely, other studies concluded that torque measurements obtained from cephalometric are predictable for clinical purposes. [7] The cephalometric analysis (T0-T1) shows that CAs are effective in retracting the maxillary incisors and improving the pro le, which is consistent with previous studies. [7]However, the angle changes of the maxillary incisors decreased by 11.68° from T0-T1, and the post-U1-NA(°)was less than the standard deviation of the normal mean, indicating that CAs were not effective in controlling incisor torque in extraction cases.…”
Section: Discussionsupporting
confidence: 90%
“…[7] The cephalometric analysis (T0-T1) shows that CAs are effective in retracting the maxillary incisors and improving the pro le, which is consistent with previous studies. [7]However, the angle changes of the maxillary incisors decreased by 11.68° from T0-T1, and the post-U1-NA(°)was less than the standard deviation of the normal mean, indicating that CAs were not effective in controlling incisor torque in extraction cases. It is possible that the overtreatment design or movement steps were not considered.The current study results indicate that there is greater upper anterior retraction in CAs.When the crown is lingually inclined ,the root will be labially inclined,which increases the risk of creating or deteriorating bone fenestration during orthodontic treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The inclusion criteria were as follows: age > 18 years, maxillary protrusion (Class I or Class II molar relationship, 2° < ANB angle < 8°, U1-NA angle > 22.8° [ 17 ], upper lips positioned in advance of the E-line), extraction of four first premolars, undergone maxillary anterior teeth retraction during orthodontic treatment, at least one maxillary anterior tooth diagnosed with PBD or LBF after orthodontic treatment, available CBCT scans before and after orthodontic treatment, and wearing a removable thermoplastic retainer during retention period. The exclusion criteria were as follows: missing maxillary anterior teeth, maxillary anterior teeth with root canal treatment and crown, significant reopening of the extraction site or crowding during the retention period, periodontal inflammation, systemic disease, and smoker.…”
Section: Methodsmentioning
confidence: 99%